EFFECT OF PLEUROTUS CITRINOPILEATUS ON BLOOD GLUCOSE, INSULIN AND CATALASE OF STREPTOZOTOCIN-INDUCED TYPE 2 DIABETES MELLITUS RATS - S. Rushita; M. Vijayakumar; A. Noorlidah; M. Ameen Abdulla; S. Vikineswary (Journal of Animal and Plant Sciences, 2013)
There is an increasing demand by patients to use natural products with hypoglycaemic activity for the treatment of diabetes mellitus. The present investigation aims at examining the hypoglycemic potential of methanolic extract of P. citrinopileatus mycelium on streptozotocin-induced type 2 diabetes mellitus rats. Oral treatment of control and diabetic rats with extract at 500 and 1000 mg/kg body weight were monitored for blood glucose, serum insulin and catalase activity. Results showed a significant reduction (P<0.05) in fasting blood glucose level and serum catalase activity but a significant increase in serum insulin level in the high dose treated group compared to untreated diabetes mellitus experimental group. Furthermore, some histopathological changes were noticed in the kidney tissue section. This study revealed P. citrinopileatus had excellent antidiabetic activity and thus have great potential as an ingredient in natural health products.
Keywords: Yellow oyster mushroom; antidiabetic activity; hypoglycemic; mycelium